The genus Systenus Meigen, 1803 (Diptera: Dolichopodidae) from Yunnan, China, with descriptions of six new species - Lin, Chen; Zhang, Chunmin; Yang, Ding (Zootaxa, 2023)
Only two species of Systenus Loew, 1857 were previously known to occur in China. Here we report Systenus from Yunnan with the following six new species: S. apicidigitatus sp. nov., S. basiflavus sp. nov., S. digitatus sp. nov., S. flavilateralis sp. nov., S. huanglianus sp. nov. and S. latimaculatus sp. nov. A key to the species of Systenus from China is provided.